PENGARUH DISIPLIN KERJA, PENDIDIKAN PEATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA BHABINKAMTIBMAS SE-KABUPATEN LAMPUNG TIMUR - Mas Agung Pribadi (Universitas Muhammadiyah Metro Lampung, 2019)
The purpose of this study was to determine the effect of work discipline, training education and work motivation on the performance of Bhabinkamtibmas in East Lampung Regency. This study uses a quantitative approach with a causality test, by testing the independent variables on the dependent variable based on the supporting theories of each variable. Data collection research using questionnaire instruments to 25 respondents. Data obtained were then analyzed using multiple linear regression tests. Based on the results of the study, it can be seen that partially the influence of work discipline, training education and work motivation on the performance of Bhabinkamtibmas East Lampung Regency based on the results of SPSS output calculation, the significance value of the t test for three variables X1 (0,000), X2 (0,000 ) and X3 (0.001) 5 0.05. So Ho is rejected so that there is an influence of work motivation, training education and work motivation on performance. For F count = 61,089 and F table (k; n-k) = (3; 25-3) = (3; 23) = 3.03. Then 61,089 ˃ 3,03 so that the variables of work discipline, training education and work motivation have a simultaneous effect on the performance variables. For the coefficient of determination R2 is 0.897 or 89.7%. This shows that the variables of work discipline, training education and work motivation have a joint effect of 89.7% on the performance of Bhabinkamtibmas East Lampung Regency, while the remaining percentage is 100% - 89.7% = 10.3% influenced by other variables not examined in this study. Keywords : Work Discipline, Training Education, Work Motivation and the Performance of Bhabinkamtibmas